Mechanisms of antimony release from lacustrine sediments with increasing temperature. (15th April 2023) - Liu, Zhenhai; Song, Lanlan; Yan, Wenming; Chen, Musong; Zhong, Zhilin; Li, Cai
Abstract: Antimony (Sb) is more mobile in lacustrine sediments with seasonal warming. However, the mechanisms of Sb mobility in sediments are still unclear, especially considering the interactions among Sb, iron (Fe), manganese (Mn), and dissolved organic matter (DOM). In this study, high-resolution dialysis (HR-Peeper) and multi-spectral techniques simultaneously investigated changes in Sb, Fe, Mn, and DOM in two different ecological types (algal and grass) sediments with increasing temperature. We found that the dissolved Sb rapidly increased with the increase in temperature. The oxidation of Sb(III) to Sb(V) by Fe/Mn oxides in oxygen (O2 ) rich overlying water and surface sediment layers was one of the reasons for Sb concentration enhancement in pore water. Further, using excitation-emission matrix and parallel factor analysis (EEM-PARAFAC), synchronous fluorescence (SF) spectroscopy, fourier transform infrared (FTIR) spectroscopy, and two-dimensional correlation spectroscopy (2D-COS) revealed that complexation with DOM was the other reasons for Sb concentration increasing in sediments. This was demonstrated by the similar distribution pattern and significant correlation between Sb and tryptophan-like components. Titration experiments further revealed that Sb was more stably bound to tryptophan-like components in the aromatic C–H (660 cm −1 ), alcoholic C–O (1115 cm −1 ), alkene CC (1615 cm −1 ), and carboxylic acid OH (3390 cm −1 ) groups. The tryptophan-like components from the algae region had a higher binding force than that from the macrophytes region. Our study effectively promotes an understanding of Sb mobilization in lacustrine sediments. Graphical abstract: Image 1 Highlights: Dissolved Sb rapidly increased with the increase in temperature. The migration of Sb in sediments was mainly controlled by the Fe and Mn oxides. Complexation with DOM was the other reason for Sb increasing in sediments. Sb(V) was more stably bound to tryptophan-like components.